METABOLIC SYNDROME AND ITS COMPONENTS IN FORMER ATHLETES: A REVIEW - Altowerqi, Zayed M; Zainuddin, Zainal Abidin bin; Hashim, Asha Hasnimy Binti Mohd; Sayyd, Sameer M (International Journal of Psychosocial Rehabilitation, 2020)
The benefits of physical activity on health are obvious in spite of the effects of participating in vigorous exercises and competitive sports in which they still remain uncertain. The present study examines the widespread presence of the syndrome and its components among former athletes, who were involved in various kind of sports. It also examines the relationship between long-term vigorous exercise training and metabolic syndrome rates and its components. The study examined 18 articles related to epidemiological studies and these articles were grouped based on the type of sport the article focused. The findings have shown that former athletes who participated in endurance training and who also participated in mixed sports have low prevalence of metabolic syndrome and its components when compared to the normal population. The findings also indicate that lower cardiovascular disease mortality is one of the main reasons for the lower metabolic syndrome percentages. On the contrary, for the former power athletes the results of researches are inconsistent. When former athletes engage in mixed sports the finding of researches show their metabolic rates are lower than the normal population. To conclude, long-term high intensity training is related to the decreasing rate of metabolic syndrome in specific groups of athletes.